2010
DOI: 10.1111/j.1469-7580.2010.01267.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Ten‐m/Odz3 in the fibrous layer of mandibular condylar cartilage during postnatal growth in mice

Abstract: It has been speculated that the mandibular condyle develops via the differentiation of the fibroblast-like cells covering the condyle into chondrocytes; however, the developmental mechanisms behind this process have not been revealed. We used laser-capture microdissection and cDNA microarray analysis to elucidate the genes that are highly expressed in these fibroblast-like cells. Among these genes, the transcription of Ten-m ⁄ Odz3 was significantly increased in the fibroblast-like cells compared with other ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…The Tenm3 gene encodes a transmembrane protein thought to function as a cell signal transducer. It is expressed in the developing murine nervous system and in the femoral cartilage of 1 day old mice …”
Section: Resultsmentioning
confidence: 99%
“…The Tenm3 gene encodes a transmembrane protein thought to function as a cell signal transducer. It is expressed in the developing murine nervous system and in the femoral cartilage of 1 day old mice …”
Section: Resultsmentioning
confidence: 99%
“…This method can overcome the problem of tissue heterogeneity by selecting defined cells to minimize contamination from neighboring unrelated tissues, providing a reliable assessment of tissue-specific gene expression. A few previous studies have involved selection of chondrocytes from skeletal tissue and analysis of gene expression by means of a qRT-PCR or microarray method [20][21][22][23][24] . Although our results indicated that expression of the caspase-3 gene was similar in allografts and isografts shortly after transplantation, we found a subsequent decrease in caspase-3 expression in the allografts over time, which was significant from postoperative day seven onward.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we cannot exclude the possibility that our identified mechanism takes place in a non-neuronal context. Recent papers have identified teneurin-3 and -4 as important players in chondrogenic differentiation (49,50). Although teneurin-1 has not been studied in chondrogenesis, the likely role of GPNMB as a key regulator in chondrogenesis could implicate a function of both proteins in this event.…”
Section: Discussionmentioning
confidence: 99%